Combinations of abstract verbs and verbs added to more than one letter in Surat Al-Baqara is a semantic study (Journal of the College of Basic Education, 2022)
In the name of God, the Most Gracious, the Most Merciful. Praise be to God, Lord of the worlds, and may prayers and peace be upon Muhammad the Sincere and Trustworthy and his good and pure family. The study of the meanings of verb structures in a surah of the Holy Qur’an is considered a basis for understanding linguistic sciences, and in understanding language from its structures, rhetoric, and methods, so the research came under the title: Abstract and additional verb structures in Surat al-Baqara a semantic study, to clarify the subtle semantic differences of most verb structures contained in Surat Al-Baqarah, and my study was not a statistical study of the Surah, and the nature of the research necessitated dividing it into two sections, the first: the significance of the structures of abstract verbs in Surat Al-Baqara. The second topic: the significance of the additional verb structures in Surat Al-Baqara. They are preceded by a preface, which is a summary of Surat Al-Baqarah. Then I concluded my research with the most important findings of the research, followed by proven sources and references. And Praise is to Allah, the Lord of the Worlds.